2022
DOI: 10.13057/biodiv/d230937
|View full text |Cite
|
Sign up to set email alerts
|

Cultural strategies of the local and transmigrant communities in dealing with land and forest fire disasters in West Kotawaringin District, Central Kalimantan, Indonesia

Abstract: Abstract. Sinta D, Iskandar J, Gunawan B. 2022. Cultural strategies of the local and transmigrant communities in dealing with land and forest fire disasters in West Kotawaringin District, Central Kalimantan, Indonesia. Biodiversitas 23: 4705-4715. The Indonesian Province of Central Kalimantan has frequently faced catastrophic land and forest fire disasters in the last two decades. In 2015, the province experienced the most extensive land and forest fire disaster in Indonesia, causing severe ecological, economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Long-term perspectives allow the identification of novel threats posed by rapid global change, and can serve as an early warning system for catastrophic ecological events (Seely, 1998;Macharia, 2004;Pamo, 2004;Pollino et al, 2007;Goodall, 2008;Liwenga, 2008;Vaarzon-Morel and Edwards, 2012;Barber et al, 2013;Leonard and Parsons, 2013;Lepofsky and Caldwell, 2013;Ruiz-Mallén and Corbera, 2013;Armatas et al, 2016;Austin et al, 2017;Farimani et al, 2017;Kainamu-Murchie et al, 2018;Kaiser et al, 2019;Arias-Bustamante and Innes, 2021;Copes-Gerbitz et al, 2021;Sinta et al, 2022). Integrating TEK into management of ecosystems affected by global change may improve outcomes, since TEK guides management actions based on ecological indicators rather than arbitrary jurisdictional or bureaucratic dictates (Bach et al, 2019).…”
Section: Identifying and Coping With Novel Threats Posed By Global Ch...mentioning
confidence: 99%
“…Long-term perspectives allow the identification of novel threats posed by rapid global change, and can serve as an early warning system for catastrophic ecological events (Seely, 1998;Macharia, 2004;Pamo, 2004;Pollino et al, 2007;Goodall, 2008;Liwenga, 2008;Vaarzon-Morel and Edwards, 2012;Barber et al, 2013;Leonard and Parsons, 2013;Lepofsky and Caldwell, 2013;Ruiz-Mallén and Corbera, 2013;Armatas et al, 2016;Austin et al, 2017;Farimani et al, 2017;Kainamu-Murchie et al, 2018;Kaiser et al, 2019;Arias-Bustamante and Innes, 2021;Copes-Gerbitz et al, 2021;Sinta et al, 2022). Integrating TEK into management of ecosystems affected by global change may improve outcomes, since TEK guides management actions based on ecological indicators rather than arbitrary jurisdictional or bureaucratic dictates (Bach et al, 2019).…”
Section: Identifying and Coping With Novel Threats Posed By Global Ch...mentioning
confidence: 99%
“…The study by Soe and Chang (2019) revealed that communities that received forestry extension services exhibited increased engagement in conservation partnership programs. Likewise, research conducted in Central Kalimantan by Sinta et al (2022) emphasized the crucial significance of forestry extension officers in improving community knowledge and skills in forest management. A study conducted in Papua by Christmas et al (2021) underscored the role of trust and cooperation building between communities and the government.…”
Section: Community Human Capital Impacts Forestry Extension Officers ...mentioning
confidence: 99%